Real queer?: sexual orientation and gender identity refugees in the Canadian refugee apparatus - Murray, David A. B. (Rowman & Littlefield International, Ltd., 2015)
An ethnographic exploration of sexual orientation and gender identity (SOGI) refugee claimants' experiences of navigating the complex discourses, protocols, practices and personnel of Canada's refugee determination system. "How do I prove I'm gay?" This is the central question for many refugee claimants who are claiming asylum on the basis of sexual orientation persecution. But what are the inherent challenges in obtaining this proof? How is the system that assesses this predicated upon homonormative frameworks and nervous borders? What is the impact of gender, race and class? What is an `authentic' sexual or gender identity and how can it be performed? Real Queer? is an ethnographic examination of the Canadian refugee apparatus analysing the social, cultural, political and affective dimensions of a legal and bureaucratic process predicated on separating the `authentic' from the `bogus' LGBT refugee. Through interviews, conversations and participant observation with various participants ranging from refugee claimants to their lawyers, Refugee Protection Division staff and local support group workers, it reveals the ways in which sexuality simultaneously disrupts and is folded into the nation-state's dynamic modes of gate-keeping, citizenship and identity-making, and the uneven effects of these discourses and practices on this category of transnational migrants
Keywords: 2000 à aujourd'hui; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; cours; histoire et politique; intersectionnalité; justice sociale; migration; migrations queer; premier cycle; périodes historiques; queer; régions géographiques; sex2283; système colonial; systèmes d'oppressions; thématiques

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle